Quantifying the effects of quadrupolar sinks via15N relaxation dynamics in metronidazoles hyperpolarized via SABRE-SHEATH. Issue 64 (14th July 2020) - Birchall, Jonathan R.; Kabir, Mohammad S. H.; Salnikov, Oleg G.; Chukanov, Nikita V.; Svyatova, Alexandra; Kovtunov, Kirill V.; Koptyug, Igor V.; Gelovani, Juri G.; Goodson, Boyd M.; Pham, Wellington; Chekmenev, Eduard Y.
Abstract : The presence of 14 N nucleus in the scalar coupling network results in a 3-fold decrease of 15 N T 1 and polarization values for all 15 N sites in 15 N2 -metronidazole versus 15 N3 -metronidazole in SABRE hyperpolarization in microtesla fields. Abstract : 15 N spin–lattice relaxation dynamics in metronidazole- 15 N3 and metronidazole- 15 N2 isotopologues are studied for rational design of 15 N-enriched biomolecules for signal amplification by reversible exchange in microtesla fields. 15 N relaxation dynamics mapping reveals the deleterious effects of interactions with the polarization transfer catalyst and a quadrupolar 14 N nucleus within the spin-relayed 15 N– 15 N network.